2004
DOI: 10.1016/j.ejheart.2003.11.012
|View full text |Cite
|
Sign up to set email alerts
|

The extent of myocardial damage assessed by contrast‐enhanced MRI is a major determinant of N‐BNP concentration after myocardial infarction

Abstract: Aims: To evaluate the relationship between N-terminal Pro-Brain Natriuretic Peptide (N-BNP) level and contrast-enhanced MRI in patients after acute myocardial infarction (MI). Methods: Eighty-two patients were studied. Venous blood samples were obtained 3 days after MI and MRI was performed from 2 to 7 days after MI, with determination of left ventricular function and acquisition of perfusion data after injection of gadolinium-DTPA. First-pass images (FPI) and Delayed contrast-enhanced (CE) images were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…Several studies reported on the role of BNP, and that of NT-pro BNP as prognosis markers for mortality after AMI [31,34] and their predictive value according to their relation with EF and LV remodeling [32,35]. Recently, Cochet et al found correlations between NT-proBNP concentrations on day 3 after AMI and LVEF and infarct size derived from the delayed ce-MR images [36], but they measured NT-pro BNP in a heterogeneous cohort of patients with the whole clinical spectrum of acute coronary syndromes and without long-term monitoring. Some clinical trials suggest that the release kinetics of cardiac markers, especially NT-pro BNP, in patients with STEMI differ from those in non-STEMI-ACS [34].…”
Section: Discussionmentioning
confidence: 96%
“…Several studies reported on the role of BNP, and that of NT-pro BNP as prognosis markers for mortality after AMI [31,34] and their predictive value according to their relation with EF and LV remodeling [32,35]. Recently, Cochet et al found correlations between NT-proBNP concentrations on day 3 after AMI and LVEF and infarct size derived from the delayed ce-MR images [36], but they measured NT-pro BNP in a heterogeneous cohort of patients with the whole clinical spectrum of acute coronary syndromes and without long-term monitoring. Some clinical trials suggest that the release kinetics of cardiac markers, especially NT-pro BNP, in patients with STEMI differ from those in non-STEMI-ACS [34].…”
Section: Discussionmentioning
confidence: 96%
“…Cardiogenic shock is the leading cause of death for patients with acute myocardial infarction (MI) and associated with loss of about 40% of the LV myocardium [16,17]. It has been suggested that the magnitude of the increase in NT-pro-BNP after MI reflects not only the size of the necrosis but also the extent of ischemic territory [18,19]. Although we did not measure directly infarct size or biomarker that reflects the extent of myocardial damage, this study revealed that increased NT-proBNP level is associated with a deteriorated left ventricular function and cardiogenic shock requiring IABP.…”
Section: Discussionmentioning
confidence: 99%
“…Cochet et al observed that NTproBNP following myocardial infarction appeared associated not only with LV ejection fraction impairment but also with the extent of myocardial damage as assessed by CE-MRI [13].…”
Section: Nt-probnp and Myocardial Ischemiamentioning
confidence: 98%
“…With regard to the use of Tn I to estimate infarct size, this factor cannot be considered alone a reliable indicator of infarct size since it is known that reperfusion induces a highly variable release of enzymes [14], whereas ejection factor is widely accepted as a surrogate of myocardial infarct extension [13,15].…”
Section: Nt-probnp and Myocardial Ischemiamentioning
confidence: 99%